Nanomaterial based self-referencing microbiosensors for cell and tissue physiology research - Shi, Jin (2012)
Physiological studies require sensitive tools to directly quantify transport kinetics in the cell/tissue spatial domain under physiological conditions. Although biosensors are capable of measuring concentration, their applications in physiological studies are limited due to the relatively low sensitivity, excessive drift/noise, and inability to quantify analyte transport. Nanomaterials significantly improve the electrochemical transduction of microelectrodes, and make the construction of highly sensitive microbiosensors possible. Furthermore, a novel biosensor modality, self-referencing (SR), enables direct measurement of real-time flux and drift/noise subtraction. SR microbiosensors based on nanomaterials have been used to measure the real-time analyte transport in several cell/tissue studies coupled with various stimulators/inhibitors. These studies include: glucose uptake in pancreatic β cells, cancer cells, muscle tissues, intestinal tissues and P. Aeruginosa biofilms; glutamate flux near neuronal cells; and endogenous indole-3-acetic acid flux near the surface of Zea mays roots. Results from the SR studies provide important insights into cancer, diabetes, nutrition, neurophysiology, environmental and plant physiology studies under dynamic physiological conditions, demonstrating that the SR microbiosensors are an extremely valuable tool for physiology research.